Pencegahan Fraud Dengan Manajemen Risiko Dalam Perspektif Al-Quran - Eko Sudarmanto; Muhammad Hariyadi (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine fraud prevention strategies with a risk management approach from the perspective of the Quran. The methodology in this research is a literature study with a qualitative approach to the analysis of deductive and inductive processes. Primary data sources consist of verses of the Quran which are used as references with explanations from several commentators, and secondary data sources consist of relevant previous scientific research works. The Al-Quran interpretation method used for analysis is the al-maudhu'i interpretation method. Fraud is an act of crime and according to sharia, there must be prevention efforts according to ability. Organizational activities always contain uncertainty which is synonymous with risk, including the risk of fraud. Management has the responsibility to manage the risks that will be faced. Risk management and internal control contribute to the implementation of good governance, with the implementation of an adequate risk management and internal control system. Several verses of the Quran and hadith can be used to implement the principles of good governance: transparency, accountability, responsibility, independence and fairness. Several risk management principles are: integrated, structured and comprehensive, tailored to user needs, inclusive, dynamic, best available information, cultural and human factors, and continuous improvement. Regarding the application of the principles of fraud prevention, verses in the Al-Quran have a perspective that is not limited to textual and contextual, but also a broader and comprehensive perspective materially and immaterially.